PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP MINAT BELI PRODUK ORIFLAME DI KOTA BATAM (Studi Kasus di SPO 1040 Oriflame Munifa Arbie) - Feliks Dabur; Theresia Yoanita Hubin; Asner Sihaloho (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study was conducted to determine the effect of product quality, price, and brand image on Purchase Interest of Oriflame Product in Batam City (Case Study at SPO 1040 Oriflame Munifa Arbie). The author used quantitative research methods with the total of respondent as many as 92 employees and data collection used questionnaires. The results of this study found that the: t count is 0,391< 1,662 with a significance rate of 0.0697 > 0.05, the conclution is that there is no positive and significant of product quality on consumer buying interest, t count of 6,848 > 1,667 with a significance rate of 0.000 < 0.05, the conclution that there are positive and significant of price on consumer buying interest, t count of 2,045 > 1,667 with a significance ratel of 0.044 < 0.05, the conclution that there are positive and significant of brand image on consumer buying interest. From the F test, it shows that the fcount for product quality, price, and brand image is F_count 85,580 > F_table 2,706 with a significance level of 0.000 < 0.05. This shows that the variables of product quality, price, and brand image simultaneously have a positive and significant effect on consumer buying interest at SPO 1040 Orifalme Munifa Arbie